The School Community Responses to the Impact of Overcrowding, Subject Streaming, and Systemic Challenges in a South African Township School - Nyathi, Patrick A.; Luvalo, Loyiso (CV Sinergi Ilmu dan Publikasi, 2026)
Overcrowding, subject streaming, and broader systemic challenges are persistent issues in many township schools across South Africa. This study aimed to examine how these factors shape teaching, learning, and learner pathways in a South African township school. Using a qualitative research design, the study collected data through semi-structured interviews with 14 participants, including the deputy principal, departmental heads, and grade 12 teachers. Interview guides served as the primary research instrument, and thematic analysis was used to analyze the data. Drawing on interviews with participants and grounded in educational theories that guide classroom management in diverse contexts, the findings reveal that while subject streaming is intended to support differentiated instruction, it often intensifies overcrowding in certain subjects, limits access to gateway subjects, and reinforces existing learner inequalities. Educators also experience increased workloads due to large class sizes and limited resources. The study concludes that although subject streaming offers some instructional efficiencies, its unintended consequences undermine equity and educational quality. A holistic reconsideration of placement practices, resource allocation, and system-level support is therefore necessary to promote fair learning opportunities in South African township schools.